The Influence of Organizational Culture and Compensation on Organizational Commitment with Job Satisfaction as Mediation - Sudirman Widhy; Hendro Yuliantoro; Muhammad Zulkarnain Anwar; Anita Maharani (The Management Journal of Binaniaga, 2021)
The purpose of this research was to explore the possibility of the emergence of organizational commitment because of the influence of organizational culture and compensation on organizational commitment, in addition to being associated with job satisfaction as a mediation. The conceptual approach referred to in discussing this research starts from organizational commitment, organizational culture, compensation and job satisfaction. This research method can be explained as initially a quantitative approach, and because of the mediation the researcher refers to the structural model. The results of this research, among others, is that job satisfaction cannot be a mediation between organizational culture and organizational commitment and between compensation and organizational commitment. This then raises the picture that the respondents involved in this research do not see the presence of job satisfaction as an intermediary, interestingly, job satisfaction also does not affect organizational commitment. The results of this research have limitations, including only one company involved in the research and the company is categorized as high risk, so there is a possibility that the proposed hypothesis cannot reflect the picture in the company.